2018
DOI: 10.1097/acm.0000000000002323
|View full text |Cite
|
Sign up to set email alerts
|

How Small Differences in Assessed Clinical Performance Amplify to Large Differences in Grades and Awards: A Cascade With Serious Consequences for Students Underrepresented in Medicine

Abstract: While students entering medical schools are becoming more diverse, trainees in residency programs in competitive specialties and academic medicine faculty have not increased in diversity. As part of an educational continuous quality improvement process at the University of California, San Francisco, School of Medicine, the authors examined data for the classes of 2013-2016 to determine whether differences existed between underrepresented in medicine (UIM) and not-UIM students' clinical performance (clerkship d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(224 citation statements)
references
References 39 publications
5
218
1
Order By: Relevance
“…Research on performance assessments suggests that small differences in assessment can result in larger differences in grades and awards received-a phenomenon referred to as the Bamplification cascade.^Teherani et al illustrate the presence of this phenomenon among URM and non-URM students in undergraduate medical education. 38 The amplification cascade holds major implications for residency selection and ultimately career progression that can disproportionately affect students from underrepresented groups. Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Research on performance assessments suggests that small differences in assessment can result in larger differences in grades and awards received-a phenomenon referred to as the Bamplification cascade.^Teherani et al illustrate the presence of this phenomenon among URM and non-URM students in undergraduate medical education. 38 The amplification cascade holds major implications for residency selection and ultimately career progression that can disproportionately affect students from underrepresented groups. Our study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The root causes of this cascade include experiences such as exposure to microaggressions from peers, faculty, and patients, as well as racism. [10][11][12][13] A curricular forum for UIM learners to discuss experiences of discrimination may benefit their wellbeing. Krieger and Sidney found that "individuals belonging to groups subjected to discrimination may be at lower risk of elevated blood pressure if they are able to articulate, rather than internalize, their experiences of discrimination."…”
Section: Introductionmentioning
confidence: 99%
“…This type of investigation was recently completed by the University of California, San Francisco School of Medicine (UCSF), which found that racial/ethnic minority medical students were not only historically less likely than White students to be selected as AOA members, but that racial/ethnic minority students were less likely to receive ratings of honors on their clinical clerkship performance evaluations. 27 Similar studies have shown that racial/ethnic minority medical students are described less favorably than their White peers in the written comments on performance evaluations, even when controlling for standardized measures of academic performance. [28][29][30] Third, chapters could ensure their leadership is appropriately diverse to reduce bias when choosing and mentoring members.…”
Section: National Aoa Society-level Reformsmentioning
confidence: 85%